2022
DOI: 10.3390/app12031596
|View full text |Cite
|
Sign up to set email alerts
|

No Association between Jump Parameters and Tissue Stiffness in the Quadriceps and Triceps Surae Muscles in Recreationally Active Young Adult Males

Abstract: While the main contributor for drop jump (DJ) performance is the calf muscle–tendon unit (MTU), for countermovement jump (CMJ) performance, it is the quadriceps MTU. However, to date, it is not clear if the muscle and/or tendon stiffness of the respective MTUs can be related to DJ or CMJ performance. Therefore, the purpose of this study was to investigate the relationships between DJ and CMJ performance parameters and tissue stiffness (i.e., muscle stiffness, tendon stiffness) of the calf MTU and quadriceps MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Finally, it is worth mentioning the study by Konrad et al (2022) [ 19 ], who found no correlation between Achilles tendon and patellar stiffness and DJ40 performance parameters (RSI, JH, and CT) using the MyotonPro. One possible explanation for this discrepancy could be (in addition to the smaller number of subjects) that their participants were physically active adults lacking experience in jumping skills, whereas our participants were young basketball players who were familiar with the DJ and good jumping technique.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Finally, it is worth mentioning the study by Konrad et al (2022) [ 19 ], who found no correlation between Achilles tendon and patellar stiffness and DJ40 performance parameters (RSI, JH, and CT) using the MyotonPro. One possible explanation for this discrepancy could be (in addition to the smaller number of subjects) that their participants were physically active adults lacking experience in jumping skills, whereas our participants were young basketball players who were familiar with the DJ and good jumping technique.…”
Section: Discussionmentioning
confidence: 97%
“…For example, several authors reported moderate positive correlations of gastrocnemius medialis muscle stiffness (measured by ultrasound shear wave elastography or SWUE) with jump height and the reactive strength index (RSI = jump height/contact time) in healthy men during a 15 cm drop jump, but not with contact time [ 21 ]. In contrast, other authors did not find any positive correlations between 40 cm drop jump performance parameters and quadriceps and triceps surae stiffness (assessed with the MyotonPRO device both at the tendons and muscle tissue) in recreationally active adult males [ 19 ].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…(3)vastus lateralis (VL): The measurements were done at lower 1/3 of the distance between the anterior superior iliac spine and lateral patella. 27 The stiffness measurement was taken with the participant in the sitting position with the knee bent at 0°( resting) and 30°, 60°, 90°(maximum isometric contraction ). The knee angle was maintained by isokinetic training equipment.…”
Section: Myotonometric Assessmentmentioning
confidence: 99%
“…Intramuscular fluid pressure can have a significant impact on muscle function, affecting the geometry of muscle fibers and, as a result, the level of produced force ( Sejersted and Hargens, 1995 ). Therefore, according to Konrad and Paternoster. (2022) , evaluating this variable could contribute to the prediction of changes in muscle performance ( Wang et al, 2017 ; Wang et al, 2017 ; Klich et al, 2019 ; Klich et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%